Analysis and numerical simulation of the limiting factors of algal blooms in Qiantang River estuary. Issue 1 (September 2020) - Li, Ruohua; Pan, Cunhong; Ge, Can; Wu, Xiuguang
Abstract: Algal blooms generally occur in lakes and reservoirs rather than macro-tidal estuary. However, algal blooms repeated in the Qiantang River estuary, a typical macro-tidal estuary, which has seriously influenced the aquatic environment and water supply in Hangzhou. A coupled hydrodynamic-ecological model was established to explore controlling factors of algal blooms in Qiantang River estuary. Environmental variables were carried to study algal growth in which nutrients, water temperature and river runoff affect algal growth strongly in Qiantang River estuary according to the modeling. High nutrient concentration and temperature promote algal growth, and river runoff inversely. Substantially reducing on nutrient inputs is required to mitigate algal blooms due to high nutrient background concentration in the estuary, among which phosphorus reduce is more effective than nitrogen. In addition, more water should be discharged from the upstream reservoirs to suppress algal blooms in the drinking water source area of Hangzhou in summer.